Factors associated with health-related quality of life in elderly patients on hemodialysis - Braga, Sonia Faria Mendes; Peixoto, Sérgio Viana; Gomes, Isabel Cristina; Acúrcio, Francisco de Assis; Andrade, Eli Iola Gurgel; Cherchiglia, Mariângela Leal (Revista de Saúde Pública, 2011)
OBJECTIVE: To identify factors associated with health-related quality of life in elderly patients on hemodialysis. METHODS: Cross-sectional study including 223 patients aged >; 60 years on hemodialysis conducted in dialysis centers in the city of Belo Horizonte, southeastern Brazil, in 2008. Health-related quality of life was measured with the Kidney Disease Quality of Life Short Form (KDQOL-SF) and the Medical Outcomes Study 36-Item Short-Form Health Survey (MOS SF-36). The three KDQOL-SF component scores measured were: kidney disease component summary (11 subscales), physical component summary (four subscales) and mental component summary (four subscales). RESULTS: Significant independent negative associations were found between the kidney disease and mental components and number of chronic diseases and treatment duration. A lower physical component was seen among women, those with more advanced age, more hospital admissions, and three or more chronic diseases. CONCLUSIONS: The finding that health-related quality of life was consistently associated with chronic diseases points to the importance of the morbidity profile in elderly patients on hemodialysis. The associated factors identified including advanced age, female gender, number of hospital admissions and treatment duration can provide input for planning health actions that can more adequately meet this populations' needs.